ANALISIS STRUKTUR PADA GENRE ABSTRAK ARTIKEL BERBAHASA INGGRIS - Wiwiek Sundari (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2008)
In academic discourse, article abstract is a genre with certain structure. This article is focused on the rhetorical structure or the move of the scientific article abstract. The data were taken from seven article abstracts in English, in one language journal. The result showed that scientific article abstract can be formed by five moves: background, statement, method, and result of the research as well as the comment about the result of the research. Not all moves can be found in one article abstract. Most of abstract consists of three or four moves. The second move -statement of the research- and the third move –method of the research are the most important part as it always appears in the whole data corpus.